A gel aspiration-ejection system for the controlled production and delivery of injectable dense collagen scaffolds. (22nd March 2016) - Kamranpour, Neysan O; Miri, Amir K; James-Bhasin, Mark; Nazhat, Showan N
Abstract: A gel aspiration-ejection (GAE) system has been developed for the advanced production and delivery of injectable dense collagen (I-DC) gels of unique collagen fibrillar densities (CFDs). Through the creation of negative pressure, GAE aspirates prefabricated highly hydrated collagen gels into a needle, simultaneously inducing compaction and meso-scale anisotropy (i.e., fibrillar alignment) on the gels, and by subsequent reversal of the pressure, I-DC gels can be controllably ejected. The system generates I-DC gels with CFDs ranging from 5 to 32 wt%, controlling the initial scaffold microstructure, anisotropy, hydraulic permeability, and mechanical properties. These features could potentially enable the minimally invasive delivery of more stable hydrogels. The viability, metabolic activity, and differentiation of seeded mesenchymal stem cells (MSCs) was investigated in the I-DC gels of distinct CFDs and extents of anisotropy produced through two different gauge needles. MSC osteoblastic differentiation was found to be relatively accelerated in I-DC gels that combined physiologically relevant CFDs and increased fibrillar alignment. The ability to not only support homogenous cell seeding, but also to direct and accelerate their differentiation through tissue-equivalent anisotropy, creates numerous opportunities in regenerative medicine.